Effectiveness of Lemongrass Aromatherapy and The 4-7-8 Breathing Technique on Post Operative Pain after General Anesthesia - Azizah, Aisyah Nur; Santoso, Budi; Pratiwi, Nesa Anggun; Azizah, Nur Mauludia (Jurnal Pendidikan Keperawatan Indonesia, 2025)
Introduction: Postoperative pain is a common clinical problem among patients undergoing surgery with general anesthesia. Compared to regional anesthesia, general anesthesia is associated with a higher intensity of postoperative pain, which may lead to delayed recovery and complications if not optimally managed. In addition to pharmacological therapy, non-pharmacological pain management strategies are increasingly recommended due to their safety, flexibility, and minimal side effects. Lemongrass aromatherapy has been reported to possess antidepressant and analgesic effects, while the 4–7–8 breathing technique is known to promote relaxation and pain control. Combining these interventions may enhance postoperative pain management. Objective: This study aimed to determine the effectiveness of a combination of lemongrass aromatherapy and the 4–7–8 breathing technique in reducing pain among patients after general anesthesia. Methods: A quasi-experimental study with a pre–post test control group design was conducted at PKU Muhammadiyah Hospital Bantul. The study population consisted of postoperative patients who received general anesthesia. A purposive sampling technique was used to recruit 34 respondents, divided equally into an intervention group (n=17) and a control group (n=17). Pain intensity was measured before and after the intervention. Data were analyzed using the Wilcoxon test for within-group comparisons and the Mann–Whitney test for between-group differences. Results: The Wilcoxon test showed a significant reduction in pain intensity in the intervention group (p=0.000) and the control group (p=0.003). The Mann–Whitney test revealed a significant difference in pain reduction between groups (p=0.026), indicating greater effectiveness in the intervention group. Conclusion: The combination of lemongrass aromatherapy and the 4–7–8 breathing technique is effective in significantly reducing postoperative pain in patients after general anesthesia